2016
DOI: 10.1161/atvbaha.116.307436
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologically Improved Contractility Protects Against Aortic Dissection in Mice With Disrupted Transforming Growth Factor-β Signaling Despite Compromised Extracellular Matrix Properties

Abstract: Objective Transforming growth factor-beta (TGF-β) is a pleiotropic cytokine having diverse roles in vascular morphogenesis, homeostasis, and pathogenesis. Altered activity of and signaling through TGF-β has been implicated in thoracic aortic aneurysms and dissections, conditions characterized by a reduced structural integrity of the wall that associates with altered biomechanics and mechanobiology. We quantify and contrast the passive and active biaxial biomechanical properties of the ascending and proximal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 35 publications
16
62
0
Order By: Relevance
“…The ability of mTOR inhibitors to modulate mechanoresponses in SMCs may relate to its beneficial effects on pathological aortic remodeling and reinforce the concepts that vascular cell activation and integrin-mediated mechanotransduction play important roles in elastin aortopathy [30,31]. Additionally, mTOR inhibition increased contractile protein expression in differentiated SMCs in vivo, though to a lesser extent than previously reported for de-differentiated cultured SMCs [28] and aortas with loss of SMC differentiation due to disruption of TGF-β signaling [32,33]. …”
Section: Discussionsupporting
confidence: 67%
“…The ability of mTOR inhibitors to modulate mechanoresponses in SMCs may relate to its beneficial effects on pathological aortic remodeling and reinforce the concepts that vascular cell activation and integrin-mediated mechanotransduction play important roles in elastin aortopathy [30,31]. Additionally, mTOR inhibition increased contractile protein expression in differentiated SMCs in vivo, though to a lesser extent than previously reported for de-differentiated cultured SMCs [28] and aortas with loss of SMC differentiation due to disruption of TGF-β signaling [32,33]. …”
Section: Discussionsupporting
confidence: 67%
“…A recent study showed that pressure-induced intramural delamination was associated with accumulation of interstitial fluid in aortic media of mice with disrupted TGF-β signaling and could be prevented in part by pharmacological improvement of SMC contractility ex vivo. 46 The results are consistent with the present hypothesis on the role of ECM contraction in limiting interstitial fluid retention and delamination. However, further studies are needed to examine whether the same results may apply to subvessel-level SMC contraction in human thoracic aorta.…”
supporting
confidence: 92%
“…28 On the other hand, active VSMC contraction may serve as a crucial protective mechanism against aortic dissection, as recently suggested by Ferruzzi and colleagues following elegant ex vivo experiments in dissection prone murine aortas. 29 …”
Section: Clinical Significance Of Arterial Stiffnessmentioning
confidence: 99%
“…62 Jay Humphrey’s group published a study in ATVB earlier this year demonstrating that postnatal disruption of TGF-β type II receptor Tgfbr2 in SMCs compromises both active (contractile) and passive (structural) biaxial biomechanical properties in the murine thoracic aorta. 29 Furthermore, they found that daily in vivo treatment with rapamycin largely preserves or restores biaxial contractile properties, but not passive structural properties.…”
Section: Underlying Mechanisms Of Arterial Stiffeningmentioning
confidence: 99%